Animals in hot and cold places - Penny, Malcolm (Wayland Hove, 1994)
Explains how animals have adapted to live in different climates, including such examples as how a walrus' blubber keeps it warm and why hippopotamuses wallow in muddy rivers. Suggested level: primary, intermediate